Clinical course, prognostic markers, and transplant implications in COVID-19-associated secondary sclerosing cholangitis - Johannes Roman Wiessner; Matthias Kis; Daniela Lenggenhager; Caecilia Sophie Reiner; Pedro David Wendel-Garcia; Katharina Endhardt; Daniel Stocker; Nadine Stanek; Georg Leinenkugel; Anna Svarin; Simon Bütikofer; Bernhard Morell; et al. (Journal of Gastroenterology, 2026)
Abstract Background Secondary sclerosing cholangitis (SSC) has emerged as a severe complication in critically ill COVID-19 patients. This study outlines the clinical course, prognostic markers, and liver transplantation (LT) outcomes of COVID-19-associated SSC. Methods This retrospective multicenter study included 36 COVID-19-associated SSC patients from three Swiss tertiary centers. Clinical, laboratory, imaging, and histopathological data were analyzed with respect to outcomes defined as survival without LT versus LT or death. Post-transplant outcomes were assessed. Results All 36 critically ill patients developed acute respiratory distress syndrome. SSC was diagnosed post-ICU in 80.6% of cases. After a median follow-up of 537 days, 12 patients died, six progressed to decompensation, 14 had compensated liver disease, and four underwent LT. Among 17 LT-evaluated patients, eight died during evaluation or on the waiting list. All four transplanted patients survived. Univariable analysis identified male sex and extent of elevated alkaline phosphatase (AP), bilirubin, aspartate aminotransferase, and alanine aminotransferase at SSC diagnosis, and at peak as predictors of poor outcomes. Histopathological features associated with adverse outcomes included portal edema and bile infarcts, whereas septal fibrosis, florid inflammation, and MRI-detected parenchymal signal changes correlated with transplant-free survival. In multivariable analysis, parenchymal signal changes (OR 0.03, 95%CI 0.00–0.83) and peak AP (OR 7.23, 95%CI 1.14–45.73) remained independently associated with outcome. Conclusions COVID-19-associated SSC carries high morbidity and mortality. Clinical, biochemical, imaging, and histopathological parameters enable early risk stratification and predict outcome. Timely LT evaluation is recommended in severe cases, given favorable post-transplant outcomes.